2020
DOI: 10.1097/md.0000000000019354
|View full text |Cite
|
Sign up to set email alerts
|

Removal of intracardiac bone cement embolism after percutaneous kyphoplasty

Abstract: Rationale: Leakage of bone cement is a common complication after percutaneous kyphoplasty. In rare cases, bone cement can leak into the venous system, which can be life threatening, especially when it causes an embolism in the heart. Patient concerns: A 79-year-old female patient developed chest pain with chest tightness 3 weeks after the percutaneous kyphoplasty. Diagnoses: Initially, negative fluoroscopy r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 18 publications
2
13
0
Order By: Relevance
“…This case suggests that when sudden loss of consciousness or other atypical symptoms occur after PVP, echocardiography should be performed as soon as possible to evaluate the cardiac status, which is consistent with the view of Song et al 5 …”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This case suggests that when sudden loss of consciousness or other atypical symptoms occur after PVP, echocardiography should be performed as soon as possible to evaluate the cardiac status, which is consistent with the view of Song et al 5 …”
Section: Discussionsupporting
confidence: 88%
“…Considering the length and location of the cement and the perforation of the heart due to the cement leakage, we performed a ruptured heart repair and tricuspid annuloplasty in this patient. This case suggests that when sudden loss of consciousness or other atypical symptoms occur after PVP, echocardiography should be performed as soon as possible to evaluate the cardiac status, which is consistent with the view of Song et al 5…”
Section: Discussionsupporting
confidence: 88%
“…Previous studies have found that most patients with ICE have dyspnea or chest pain as the first symptoms after PVP, [5][6][7][8] the duration of onset is inconsistent, and rare cases may be asymptomatic. 6 But no matter what the clinical symptoms are, the most urgent need is for early detection and immediate treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Xray has special advantages for the discovery of metallic foreign bodies, but it can usually not determine the specific location of the mass in the heart cavity, and some chest X-rays only show thickening of lung texture. 8 Chest CT can confirm the location of cement emboli in the heart, and at the same time can judge whether there is pulmonary embolism, 5,7-8 but it takes a long time for the examination and the results to be obtained, and it is impossible to observe the immediate changes of the foreign body.…”
Section: Discussionmentioning
confidence: 99%
“… 2 During the embolization, the cement migrates through the paravertebral or epidural veins into the venous system and embolizes in the direction of the right heart or pulmonary arteries. 3 Even if cement embolization is often asymptomatic, there is a risk of a fulminant course. Several risk factors have been identified for the occurrence of a cement embolism.…”
Section: Introductionmentioning
confidence: 99%